FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN DAN PERILAKU KONSUMEN RUMAH TANGGA TERHADAP DAGING SAPI DI KABUPATEN JEMBER - Septian Maulana Purnama; Rudi Wibowo; Ati Kusmiati (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2016)
Beef is one of the food requirements strategically in Indonesia. Consumption of beef each year has increased, while the price of beef also increased, it is contrary to the demand theory. The purpose of this research to know (1) what factors that influence the beef demand in Jember Regency; (2) what factors that influence the behavor of household consumer to consume in Jember Regency (3) preference of household consumer behavior for beef in Jember Regency The research method uses descriptive method and analytic method. The Data analysis use Multiple Linear Regression Analysis, Factor Analysis and Fishbein Multiatribut Analysis. Results from this study indicate (1) the factors affecting demand, namely, income level, chicken meat prices, and population (2) factors that influence the behavior of household consumers to consume in Jember: cultural factor, external character factors of consumers, social factors, the perception factor, privacy factor and motivation factors (3) Household consumer preferences for beef of three variables alternately; piece of meat, meat color and fat content.